Soil microbial biomass and bacterial diversity in southern European regions vulnerable to desertification. (December 2022) - Catania, V.; Bueno, R.S.; Alduina, R.; Grilli, E.; La Mantia, T.; Castaldi, S.; Quatrini, P.
Highlights: Soil microbial biomass is positively correlated to SOC and TN. Bacterial diversity is negatively correlated to SOC. pH was the most influencing factor positively affecting bacterial alpha-diversity. A core microbiota was identified in semi-arid soils of Southern Europe. We provide baseline data for the monitoring of EU soils facing desertification. Abstract: Soil functionality is strongly dependent on the soil microbiota, which in turn is affected by soil quality and climate. Among global change factors, desertification is the most threatening ecosystem change affecting southern Europe, but the effects on the soil microbiota are largely unknown. In this study, we investigated soil microbial biomass and bacterial diversity in regions of southern European countries (Spain, Portugal and Italy), most under desertification risk, and related to key soil chemical-physical indicators and land use. Soil microbial biomass was positively related to soil organic carbon (SOC), but bacterial diversity was negatively correlated with it. pH was the most influencing factor affecting soil alpha-diversity, while SOC, pH and cation exchange capacity drive the biogeographic patterns of bacterial communities. 16S rRNA gene metagenomics allowed the identification of a core microbiota of the analyzed semi-arid soils, including Proteobacteria, Actinobacteria, Acidobacteria and Firmicutes. We identified, at regional scale, a few rare multi-extremophilic endemic genera, which could reveal functional strategies to be exploited for arid land restoration. This work creates the baseline for the necessary monitoring of soils facing climate change and for the evaluation of the efficacy of adaptation measures in semi-arid European soils.